Effect of Rice Beer and Phyto-ingredients on Microbiological Qualities of Vacuum and Aerobically Packaged Marinated Duck Meat - Pompi Rani Boro; Saurabh Kumar Laskar; Ankur Das; Rita Nath; Naba Jyoti Deka (Archives of Current Research International, 2025)
This research was carried out to investigate the effect of incorporating rice beer and phyto-ingredients on the microbiological qualities of vacuum packaged marinated duck meat. Ducks aged between 9 and 12 months were procured from a local market and hygienically slaughtered and dressed. Five batches of marinated duck meat were prepared, each consisting of four different treatments. Following slaughter and dressing, the ducks were marinated using four altered formulations: a control group (meat + spice paste), T1 (meat + rice beer + spice paste), T2 (meat+ phyto-ingredients + spice paste), and T3 (meat + rice beer + phyto-ingredients + spice paste). These marinated meat samples were then vacuum-packaged and stored under refrigeration for24 hours. Subsequent quality assessments were carried out on the samples at 5 days intervals for the vacuum-packed samples.The microbiological quality studies revealed that there is a significant increase (P<0.01) in control samples compared to treated samples during the entire storage periods in both the packaging systems, whereas, total psychrophilic count could not be detected on 1stand 5th day of storage in vacuum packaging but on 10th and 15th day it increases in the storage periods. Similarly for aerobically packaging systems, Total viable mesophilic plate count (TVMPC) were not detected on 1st day of storage but on 3rd, 5th and 7th day of storage it increases in the storage periods. The yeast and mould count and Coliform count were absent in all the storage periods in both the packaging systems. The sulphite reducing Clostridial organisms and Salmonella were also found to be absent in all the samples for both the packaging systems.